Analysis Validity and Readability of STEM-Based Virtual Laboratory Lab Gene Learning Media on Modern Biotechnology Materials to Improve Science Literacy of High School Students - Sholeha, Siti; Rahayu, Enni Suwarsi; Yuniastuti, Ari; Rusilowati, Ani (Universitas Negeri Semarang, 2024)
The Learning based on the Merdeka Belajar Curriculum allows students to be more independent in choosing their learning resources. Modern biotechnology practicum is often not carried out due to expensive tools and materials, and is usually incomplete. Teachers tend to only focus on the application of conventional biotechnology, and do not explore modern biotechnology. In addition, the science literacy skills of students in schools are still low, and there is no virtual laboratory learning media that can be used by students to improve understanding of modern biotechnology concepts for understanding biological technology innovation in CP phase F. This study aims to test the validity and openness test of STEM-based Lab Gene virtual laboratory learning media on modern biotechnology material. Data analysis was conducted to measure the validity and readability of the learning media. The results showed that the validity value of Lab Gene was declared valid with a value of 90.10% or including a very high category (very valid) by material experts and 83.75% or including a very high category (very valid) by media experts. Meanwhile, the results of media readability (rumpang analysis) by 9 students at SMAN 1 Sumber obtained 89.03% with a very good category. Based on the research results, it is known that the STEM-based Lab Gene virtual laboratory is said to be valid and has good readability. Lab Gene virtual laboratory learning media is feasible to be implemented in schools to improve students’ science literacy.